Pengaruh Program Pengembangan Usaha Agribisnis Perdesaan (PUAP) terhadap Produksi dan Pendapatan Petani Padi (Studi Kasus : Gapoktan Belega Mandiri di Desa Belega, Kecamatan Blahbatuh, Kabupaten Gianyar) - ULANDARI, NI PUTU RISKIANA; ANTARA, MADE; DJELANTIK, A.A. AYU WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.2, April 2018, 2018)
The Effect of Pengembangan Usaha Agribisnis Perdesaan (PUAP) Program on the Rice Farmers' Production and Income (Case Study: Gapoktan of Belega Mandiri in Belega Village, Blahbatuh Sub-District, Gianyar Regency) Pengembangan Usaha Agribisnis Perdesaan (PUAP) Program is a form of facilitation of business capital assistance for member farmers, either farmers, peasants, farm workers and farm households coordinated by the Gabungan Kelompok Tani (Gapoktan). This research was conducted to investigate the effect of PUAP program on the production and income of rice farmers in the Joint Farmer Group of Belega Mandiri. The analytical method used to investigate the effect of PUAP on production was multiple linear regression analysis with Cobb-Douglas production function model in the form of natural logarithm, while to analyze the effect of PUAP on income was done by comparative analysis on cost, revenue, income, and total of R/C. The findings showed that PUAP has a significant effect on rice production in the Joint Farmer Group of Belega Mandiri. In addition to PUAP, factors affecting rice production include seeds and labors. The average cost, revenue, and income of PUAP users per hectare was higher than those of non-PUAP users. The t-test results showed that the average total of R/C value between the PUAP users and non-PUAP users was significantly different. This indicates that farming of PUAP users were more efficient than those of non-PUAP users.